Challenges and Strategies for Implementing Education Management in the Digital Age: A Review of Curriculum Innovation and Development - Desi Ratna Sari (Pt. Anagata Sembagi Education, 2024)
The digital age not only transforms the way we learn but also undergoes changes in educational system management. In an environment influenced by globalization and technological advancements, educational institutions must adapt to more adaptive and innovative models. Educational managers must continually update their strategies and practices to remain relevant and effective in delivering quality education. The importance of educational inclusion in the digital era takes center stage. Despite technology opening access to educational resources for many individuals, challenges remain in ensuring equal access for all, including those in remote areas or with special needs. Therefore, educational management in the digital age must consider the need for justice and inclusion in providing educational services. In the context of higher education, universities are also faced with the demand to prepare graduates with skills relevant to the ever-changing job market. The development of relevant curricula, project-based learning, and partnerships with industries become primary focuses. Cybersecurity challenges also take top priority, given the vulnerability of educational institutions to cyberattacks. It is important to acknowledge that implementing educational management in the digital age also involves cultural and mindset changes within educational institutions. Educational leaders must become progressive change agents and be open to innovation. By fostering a culture of collaboration, experimentation, and continuous learning, the educational environment can become dynamic and responsive to present and future challenges.